2015
DOI: 10.1002/ange.201506902
|View full text |Cite
|
Sign up to set email alerts
|

The First Crystal Structure of a Reactive Dirhodium Carbene Complex and a Versatile Method for the Preparation of Gold Carbenes by Rhodium‐to‐Gold Transmetalation

Abstract: The dirhodium carbene derived from bis(4‐methoxyphenyl)diazomethane and [Rh(tpa)4]⋅CH2Cl2 (tpa=triphenylacetate) was characterized by UV, IR, and NMR spectroscopy, HRMS, as well as by X‐ray diffraction. The isolated complex exhibits prototypical rhodium carbene reactivity in that it cyclopropanates 4‐methoxystyrene at low temperature. Experimental structural information on this important type of reactive intermediate is extremely scarce and thus serves as a reference point for mechanistic discussions of rhodiu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(7 citation statements)
references
References 73 publications
0
7
0
Order By: Relevance
“…49 The few reported X-ray structures of dirhodium carbenes crystallize as coordination polymers: OMe or NMe2 groups present in the carbene appendants coordinate to the rhodium not bearing the carbene carbon of the next unit. 50,51 These complexes require CH2Cl2 and toluene to be stable in crystalline form and their unit cells contain highly disordered solvent molecules. 50 In solution, axial solvent coordination to dirhodium complexes is well known, [52][53][54][55][56] and even macroscopically evident due to its effect on the electronic structure of the complex.…”
Section: Overview and Historical Contextmentioning
confidence: 99%
“…49 The few reported X-ray structures of dirhodium carbenes crystallize as coordination polymers: OMe or NMe2 groups present in the carbene appendants coordinate to the rhodium not bearing the carbene carbon of the next unit. 50,51 These complexes require CH2Cl2 and toluene to be stable in crystalline form and their unit cells contain highly disordered solvent molecules. 50 In solution, axial solvent coordination to dirhodium complexes is well known, [52][53][54][55][56] and even macroscopically evident due to its effect on the electronic structure of the complex.…”
Section: Overview and Historical Contextmentioning
confidence: 99%
“…48 The few reported X-ray structures of dirhodium carbenes crystallize as coordination polymers: OMe or NMe2 groups present in the carbene appendants coordinate to the rhodium not bearing the carbene carbon of the next unit. 49,50 These complexes require CH2Cl2 and toluene to be stable in crystalline form and their unit cells contain highly disordered solvent molecules. 49 In solution, axial solvent coordination to dirhodium complexes is well known, [51][52][53][54][55] and even macroscopically evident due to its effect on the electronic structure of the complex.…”
Section: Overview and Historical Contextmentioning
confidence: 99%
“…49,50 These complexes require CH2Cl2 and toluene to be stable in crystalline form and their unit cells contain highly disordered solvent molecules. 49 In solution, axial solvent coordination to dirhodium complexes is well known, [51][52][53][54][55] and even macroscopically evident due to its effect on the electronic structure of the complex. Coordination by solvent molecules is comparatively much weaker than carboxylate coordination.…”
Section: Overview and Historical Contextmentioning
confidence: 99%
“…In 2007, Gois and Jang groups reported, respectively, that the binuclear Rh(II) complex, V, containing N-Heterocyclic Carbenes (NHC) as auxiliary ligands, can be a profitable tool in (i) the arylation of aldehydes and (ii) the allylic oxidation reaction [49,50]. Recently, Werlé et al reported that acetate rhodium derivatives like compound VI can be useful carbene transfer reagents [51].…”
Section: Introductionmentioning
confidence: 99%